Effective and Safe Treatment of Risky Localized Liver Tumors Using Microwave Ablation in Patients with Comorbid Lung Diseases Unfit for Deep Anesthesia - Murat ASIK (Medeniyet Medical Journal)
Objective: To assess the safety and efficacy of percutaneous microwave ablation (MWA) in treating high-risk localized liver tumors in patients unable to undergo deep anesthesia because of comorbid lung diseases. Methods: Between January 2019 and January 2022, percutaneous MWA procedures were performed for 50 liver tumors. These lesions were situated in close proximity to anatomically essential structures, with a maximum distance to surrounding structures being 10 mm. Because of comorbid lung diseases, patients could not undergo deep anesthesia. Regular follow-ups were performed using blood tests and dynamic contrast-enhanced computed tomography or magnetic resonance imaging. Results: The patient cohort consisted of 30 (68%) men and 14 (32%) women, with a mean age of 64.36+-11.65 years (range: 40-80 years). The lesions were challenging to access and were located in proximity to critical structures such as the diaphragm (32, 64%), gallbladder (8, 16%), major vessels (5, 10%), and heart (5, 10%). During the follow-up period, 10 patients (23%) had local tumor recurrence and 14 (32%) had new primary foci in a different location and metastasis [liver (10) and non-liver organs (4)]. No major complications developed, and 21 of 44 patients experienced minor complications, which were treated with local medications during follow-up. Conclusions: Percutaneous MWA results in very low mortality and morbidity, coupled with high complete ablation rates for liver cancer. Most liver tumors can be treated safely and effectively with percutaneous MWA, even in cases of high-risk localization, without the need for deep anesthesia.